The Understanding Abilities of Real Number Concepts For Primary School Student - Khathibul Umam Zaid Nugroho; Saleh Haji (Annals of Mathematical Modeling, 2022)
The purpose of this study was to determine the characteristics of relational elementary students in understanding the concept of real numbers. This research is an exploration of the research subject. The subjects of this study were students of MIN 2 Bengkulu Selatan. There is one realistic student in this research. The researcher is the main instrument in this research which is supported by an interview guide and an assignment sheet on the concept of real numbers. The data were analyzed qualitatively. The results of this study are that students with relational abilities can combine separate pieces of information to produce the completion of a task. Therefore it is suggested to teachers and researchers of mathematics education to explore students' mathematical cognitive processes before determining the learning strategies to be carried out.